PELAKSANAAN PENDIDIKAN KARAKTER TERHADAP PESERTA DIDIK DI SMK KRISTEN AGAPE PATRIA SOSOK - Ambrosius Siligar (Sekolah Tinggi Teologi Excelsius, 2021)
Abstract: National education aims to develop the potential of students to become human beings who believe, fear Almighty God, have a noble character, are informed, capable, creative, independent, and become democratic and responsible citizens. The formulation of the research is as follows: What is the form of character education carried out at the Agape Patria Gambar Christian Vocational School? How is character education applied to student intelligence at Agape Patria Figure Christian Vocational School? This study uses a descriptive approach. Answers: (1) The form of character education provided at Agape Patria Christian Vocational High School is as follows: the honesty of students at Agape Patria Christian Vocational High School is doing well, the discipline of students at Agape Patria Christian Vocational High School school is going well and the responsibilities of the students of the Agape Patria Christian Vocational High School are good. (2) The application of character education to the intelligence of students at Agape Patria Christian Vocational School is: (a) in the character of honesty, students begin to study seriously and work hard to obtain pure grades from the results of tests and examinations carried out outside. (b) in the character of discipline, students begin to learn to live a disciplined life because it has been taught and practiced by educators and students. (c) in a responsible character by teaching and giving examples to educators on how to be responsible for something, hoping for significant changes and progress. (d) the implementation of honest, disciplined, and responsible character education for students, through a long process, will have an impact on increasing general intelligence. Pendidikan nasional bertujuan untuk mengembangkan potensi peserta didik agar menjadi manusia yang beriman, bertakwa kepada Tuhan Yang Maha Kuasa, berakhlak mulia, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggung jawab. Rumusan penelitian berikut: Bagaimanakah bentuk pendidikan karakter yang dilaksanakan di SMK Kristen Agape Patria Sosok? Bagaimanakah penerapan pendidikan karakter terhadap kecerdasan siswa di SMK Kristen Agape Patria Sosok? Penelitian ini menggunakan pendekatan deskriptif. Jawaban: (1) Bentuk pendidikan karakter yang dilaksanakan di SMK Kristen Agape Patria Sosok adalah: kejujuran siswa SMK Kristen Agape Patria berjalan dengan baik, kedisiplinan siswa SMK Kristen Agape Patria berjalan dengan baik, dan tanggung jawab siswa SMK Kristen Agape Patria adalah baik. (2) Penerapan pendidikan karakter terhadap kecerdasan siswa di SMK Kristen Agape Patria Sosok adalah: (a) dalam karakter kejujuran, siswa mulai belajar dengan sungguh-sungguh dan bekerja keras untuk memperoleh nilai murni dari hasil ulangan dan ujian yang dilaksanakan. (b) dalam karakter disiplin, siswa mulai belajar menjalani kehidupan yang disiplin karena telah diajarkan dan diamalkan oleh pendidik dan siswa. (c) dalam karakter bertanggung jawab dengan mengajarkan dan memberi contoh kepada pendidik tentang bagaimana bertanggung jawab terhadap sesuatu, semoga mengalami perubahan dan kemajuan yang berarti. (d) melaksanakan pendidikan karakter jujur, disiplin dan tanggung jawab kepada siswa, melalui proses yang panjang, akan berdampak pada peningkatan kecerdasan secara keseluruhan.